2005
DOI: 10.1136/bjo.2004.049478
|View full text |Cite
|
Sign up to set email alerts
|

Falls and health status in elderly women following first eye cataract surgery: a randomised controlled trial

Abstract: Background/aim: A third of elderly people fall each year. Poor vision is associated with increased risk of falls. The authors aimed to determine if first eye cataract surgery reduces the risk of falling, and to measure associated health gain. Methods: 306 women aged over 70, with cataract, were randomised to expedited (approximately 4 weeks) or routine (12 months wait) surgery. Falls were ascertained by diary, with follow up every 3 months. Health status was measured after 6 months. Results: Visual function im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
284
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(299 citation statements)
references
References 38 publications
7
284
1
7
Order By: Relevance
“…Province et al (1995), Gillespie et al (2001), Li et al (2005), Faber et al (2006) suggested that significant improvements in risk of falls can be achieved through exercise programs, although this finding is not universal (Cumming et al, 2007). However, there have been few studies aimed at decreasing the risk of falls by improving visual function (Day et al, 2002;Harwood et al, 2005;Foss et al, 2006). Some of these have been limited by the poor followup for treatment (Day et al, 2002) or dealt only with cataract surgery (Harwood et al, 2005;Foss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Province et al (1995), Gillespie et al (2001), Li et al (2005), Faber et al (2006) suggested that significant improvements in risk of falls can be achieved through exercise programs, although this finding is not universal (Cumming et al, 2007). However, there have been few studies aimed at decreasing the risk of falls by improving visual function (Day et al, 2002;Harwood et al, 2005;Foss et al, 2006). Some of these have been limited by the poor followup for treatment (Day et al, 2002) or dealt only with cataract surgery (Harwood et al, 2005;Foss et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies aimed at decreasing the risk of falls by improving visual function (Day et al, 2002;Harwood et al, 2005;Foss et al, 2006). Some of these have been limited by the poor followup for treatment (Day et al, 2002) or dealt only with cataract surgery (Harwood et al, 2005;Foss et al, 2006). The randomized controlled trial by Cumming et al (2007) took a more comprehensive approach to diagnosing and intervening upon vision abnormalities for the prevention of falls in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in postural stability 8,9 and reduction of fall-related injuries and risk of fractures 10 are among the advantages achieved following this operation, and should be considered in the decision to perform cataract surgery in the very elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Zu den bedeutenden klientenzentrierten Endpunkten zählen z.B. die Anzahl an Stürzen (McMurdo et al, 1997;Harwood et al, 2005;Lord et al, 2005;Porthouse et al, 2005;Swanenburg et al, 2007), die Anzahl an Gestürzten (McMurdo et al, 1997;Harwood et al, 2005;Porthouse et al, 2005), die Sturzangst (Porthouse et al, 2005;Lannin, Clemson, McCluskey, Lin, Cameron, & Barras, 2007;Lin, Wolf, Hwang, Gong, & Chen, 2007) sowie die Lebensqualität (Gallagher & Brunt, 1996;Harwood, Foss, Osborn, Gregson, Zaman, & Masud, 2005;Lannin et al, 2007) und Mobilität (Lannin et al, 2007). Da die individuelle Partizipation und Teilhabe von Klienten/-innen am Leben in der Gesellschaft Handlungsmaxime und fester Bestandteil der Sozialgesetzgebung (SGB IX) sind, sind Endpunkte, die soziale Partizipation und Wertvorstellungen abbilden, stärker in den Fokus zu rücken (BAR, 2008;Welti, & Fuchs, 2007).…”
Section: Klientenzentrierte Endpunkteunclassified